Analyzing National Health Insurance-Covered Pap Smear Initiative in Yogyakarta, Indonesia: A SWOT Perspective - Al-Naday, Qotru; Jihan Dampi, Denada; Fashani, Yuliana (BKM Public Health and Community Medicine, 2024)
Purpose: The aim of this program is to analyze the success of the Pap smear program in Yogyakarta. Content: Cervical cancer is one type of cancer that grows in the lining of the cervix. Approximately, 15,000 cases of cervical cancer are reported each year in Indonesia. The cervical cancer screening program in Yogyakarta, utilizing the Pap smear method, has been implemented to enhance early detection and management of cervical cancer. This initiative is conducted by various healthcare facilities, including community health centers (puskesmas) and hospitals, with support from the government and non-profit organizations. The impact on the community has been significant, it can reduce cervical cancer and mortality, improved survival rates, and they reduce the need for more extensive and expensive treatments required for advanced-stage cancers. However, these programs have several weaknesses that could become threats, such as limited access to healthcare facilities in remote areas, and societal stigma and fear associated with medical procedures. Pap smear screening covered by National Health Insurance (JKN) can increase people's awareness and change the stigma about pap smears. Conclusion: Although the program faces various hurdles, the Pap smear screening initiative in Yogyakarta has shown positive results in improving women's health and needs to be continuously strengthened and expanded to achieve maximum benefits.